Reduction of Severe Hypoglycemic Events Among Outpatients with Type 2 Diabetes Following Sodium-Glucose Cotransporter 2 Inhibitor Marketing in Japan - Yamashita, Koh; Yoshiike, Shouichi; Yamashita, Taku; Mori, Jun-ichirou; Aizawa, Toru (Hormone and Metabolic Research, 2022)
Recently, oral hypoglycemic agents with newer glucose lowering mechanisms have been on release. This is mostly to meet the diabetic patient’s need to avoid hypoglycemia, which is profoundly important for better long-term outcome of the treatment. In this study, we quantified the annual number of patients with type 2 diabetes who experienced hypoglycemia needing the third-party assistance who had random sample plasma glucose<59.4 mg/dl (3.3 mmol/l) on the one hand and analyzed the prescription trend of hypoglycemic agents all over Japan on the other. Analysis of the annual number of hypoglycemic patients visited ER was performed at Aizawa Hospital, a medical center located in the midst of a city. The study duration was over 10 years from 2008 to 2019. We found a clear-cut decreasing trend of hypoglycemia over the 10 years, ca. 61/year to 39/year. Immediately after the release of sodium-glucose co-transporter-2 inhibitors, since 2013 to 2017, the decrease was rather sharp as 81/year to 31/year, and the change of the national number of its prescription inversely correlated with the change of the number of the patients with hypoglycemia. This was not the case immediately after the introduction of dipeptidyl peptidase-4 inhibitors in the Japanese market since 2008 to 2012. There was no significant correlation between its prescription and the number of patients with hypoglycemia. The data strongly suggested that there was a causal relationship exclusively between the introduction of sodium-glucose cotransporter-2 inhibitor, and the reduction of hypoglycemic events among patients with type 2 diabetes.
Keywords: etiology; adverse effects; complications